2021
DOI: 10.1111/padm.12804
|View full text |Cite
|
Sign up to set email alerts
|

Financial reporting transparency, citizens' understanding, and public participation: A survey experiment study

Abstract: This study investigates the conditions under which transparency contributes to citizens' understanding of financial reporting and examines how this enhanced understanding is associated with public participation. To this end, a survey experiment was conducted in which two attributes of financial reporting transparency (i.e., content clarification and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 96 publications
(140 reference statements)
3
20
0
7
Order By: Relevance
“…However, research demonstrating that the same benefits are also evident in relation to public sector financial accounting information is still in its infancy. Langella et al (2021) provide evidence that graphical and visual representations increase financial statements' understandability. However, they also evidence that there is no additional benefit in financial reporting understandability when simultaneously providing both explanations of technical jargon and visual aids.…”
Section: Accounting Understandability and Infographicsmentioning
confidence: 92%
See 3 more Smart Citations
“…However, research demonstrating that the same benefits are also evident in relation to public sector financial accounting information is still in its infancy. Langella et al (2021) provide evidence that graphical and visual representations increase financial statements' understandability. However, they also evidence that there is no additional benefit in financial reporting understandability when simultaneously providing both explanations of technical jargon and visual aids.…”
Section: Accounting Understandability and Infographicsmentioning
confidence: 92%
“…The layout of popular reports aims to constitute a user-friendly interface which is also achieved by the adoption of visuals. Moreover, the use of visual aids and graphical representations enhances the informativeness of financial reports (Langella et al, 2021). Even JPBAFM 34,6 though the use of infographics has not been yet assessed as a means to convey accounting information, studies have shown that visuals are easier to comprehend and, as a consequence, infographics may provide a superior communication tool to text (Young and Hinesly, 2014).…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…They chose any number of options within the multiple-choice question: What would change your perception of taxes? Eight predefined answers were selected based on a literature search (Grimmelikhuijsen & Meijer, 2012;Langella, C. et al, 2021;Kim and Lee, 2012;Brown, 1979;Dahlby 2002) Cochran's Q non-parametric statistical test on the significance level of 0.05 is used to determine whether the proportion of successes of facilitating the perception of taxes is equal across eight groups mentioned above (1)-( 8). H0: The proportion of successes is equal for all the groups.…”
Section: Methodsmentioning
confidence: 99%